n Kaok - Mulheres Fortes: uma etnografia das práticas e saberes extra-ordinários das mulheres tikmn maxakali - Claudia Magnani (2018)
On Amerindian ethnology, an awe towards the exotic and for great themes such as war and ritual led to a systematic lack of interest on domesticity and daily life (OVERING, 1999), as those domains are identified (sometimes even disqualified) as familiar, profane, ordinary; thus, without greater social, symbolic or cosmological density. However, this epistemological glitch is more revealing of an androcentric ethnographical gaze, typical of the Western historical and cultural tradition, than of a native perspective of the world, built on their philosophical framings and categories. By means of a critical reading of the studies on the Tikmn-Maxakali and an ethnographic experience carried out at the village of Aldeia Verde, this work aims to deconstruct ethnographic prejudices and to resignify female practices and knowledges. The home visits, the daily commensality, the family care, the kinship networks, as well as the urucum paint preparation, clay pots making or embaúba fiber weaving crafts are part of a female agency that transcends mere utilitarian, physiological of family caring functions. Feeding (or not) their relatives, being together or apart, weaving the fiber or burning the clay, the women product, assure or threat the sociality among humans and, at the same time, the relations with the yãmyxop-spirits (and the countless subjectivities that share their world). Although liminal, peripheral, domestic, daily tikmn womens acts are divergent but not opposite or less important than mens acts. They are equally vital to the maintenance of the ordinary and extraordinary worlds, which are not disjoint ones. Finally, oppositions like daily life versus ritual, men versus women and private versus political became meaningless, giving way to relations of contiguity and complementarity, more appropriated ways to translate the fluid, shared, ambivalent and malleable dimensions of native experience